Wind Turbines - Frede Blaabjerg (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This issue is a continuation of the previous successful Special Issue "Wind Turbines 2013". Similarly, this issue also focuses on recent advances in the wind energy sector on a wide range of topics, including: wind resource mapping, wind intermittency issues, aerodynamics, foundations, aeroelasticity, wind turbine technologies, control of wind turbines, diagnostics, generator concepts including gearless concepts, power electronic converters, grid interconnection, ride-through operation, protection, wind farm layouts - optimization and control, reliability, operations and maintenance, effects of wind farms on local and global climate, wind power stations, smart-grid and micro-grid related to wind turbine operation.